Novel Edible Coating of Starch-Based Stenospermocarpic Mango Prolongs the Shelf Life of Mango “Ataulfo” Fruit - Sara Elena Hernández-Guerrero; Rosendo Balois-Morales; Yolotzin Apatzingán Palomino-Hermosillo; Graciela Guadalupe López-Guzmán; Guillermo Berumen-Varela; Pedro Ulises Bautista-Rosales; Gelacio Alejo-Santiago (Journal of Food Quality)
Edible coatings based on 2% starch (w/v) extracted from tropical fruits were applied on stenospermocarpic mango fruits with the objective to prolong its shelf life during storage and give them an added value since they have no commercial value. In this regard, stenospermocarpic mangoes were coated with starch from banana “Pear” (T1 and T2), starch from soursop (T3 and T4), and starch from stenospermocarpic mango (T5 and T6), and two uncoated control treatments (T7 and T8). The fruit of T1, T3, T5, and T7 treatments were stored for 15 days (10 days at 10 ± 2°C and then at 22 ± 2°C for 5 days). The fruit of T2, T4, T6, and T8 treatments were stored for 10 days at 22 ± 2°C. Data were analyzed with a 4×2 factorial experimental design. Weight loss (g), firmness (N), total soluble solids content (%), titratable acidity (%), and color (L∗h∗C∗) were evaluated. The fruit coated with mango starch (T5) showed less weight loss (2.57%), greater firmness (18.6 N), as well as a high content of TSS (28.76%) compared with the control. The T5 extended the shelf life of the fruit up to 15 days (10 days at 10 ± 2°C and 5 days at 22 ± 2°C).